Laparoscopic vs Open Ultrasound of the Liver: An in vitro Study. Issue 2 (1996) - Cozzi, P. J.; McCall, J. L.; Jorgensen, J. O.; Morris, D. L.
Abstract : Intra-operative contact ultrasound is a sensitive method of detecting liver tumours. The aim of this study was to compare the sensitivity of open contact ultrasound (OUS) of the liver with laparoscopic contact ultrasound (LUS). Hypoechoic "lesions" were created in 5 fresh pig livers by inserting 28 grapes via small incisions in the inferior surface. The size (range 8–25 mm) and location of each grape was recorded. Scanning was undertaken in random order by two experienced independent observers with no knowledge of the size, number or position of the lesions, using an Aloka 650 series scanner and 7.5 MHz probes. The crude sensitivity with OUS was 96% and 100% respectively for the two observers, and 92% for each with LUS. One grape was interpreted as 2 seperate grapes on LUS by one observer. Absolute sensitivity (grapes identified in the correct location) was 86% and 93% respectively with OUS and 79% for each observer with LUS. LUS was almost as sensitive as OUS in this model of hepatic metastases.